Increasing the economic development benefits of higher education in Michigan - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2004)
This paper considers how a state such as Michigan can increase the economic development benefits of higher education. Research evidence suggests that higher education increases local economic development principally by increasing the quality of the local workforce, and secondarily by increasing local innovative ideas. These economic development benefits of higher education can be increased by: 1) competent management of conventional economic development programs that focus on business attraction and retention; 2) policies that focus on increasing local job skills by educating the state's residents, as opposed to attracting in-migrants; 3) policies that address specific 'market failures' in how higher education leads to increased workforce quality or business innovations.
Keywords: R58; I28; H72; 330; Studium; Regionale Entwicklung; Bildungsinvestition; Michigan